Gardenia jasminoides extract and its constituent, genipin, inhibit activation of CD3/CD28 co-stimulated CD4 + T cells via ORAI1 channel - Kim, Hyun Jong; Nam, Yu Ran; Woo, JooHan; Kim, Woo Kyung; Nam, Joo Hyun (The Korean journal of physiology & pharmacology, 2020)
Gardenia jasminoides (GJ) is a widely used herbal medicine with antiinflammatory properties, but its effects on the ORAI1 channel, which is important in generating intracellular calcium signaling for T cell activation, remain unknown. In this study, we investigated whether 70% ethanolic GJ extract (GJEtOH) and its subsequent fractions inhibit ORAI1 and determined which constituents contributed to this effect. Whole-cell patch clamp analysis revealed that GJEtOH (64.7% ± 3.83% inhibition at 0.1 mg/ml) and all its fractions showed inhibitory effects on the ORAI1 channel. Among the GJ fractions, the hexane fraction (GJHEX, 66.8% ± 9.95% at 0.1 mg/ml) had the most potent inhibitory effects in hORAI1-hSTIM1 co-transfected HEK293T cells. Chemical constituent analysis revealed that the strong ORAI1 inhibitory effect of GJHEX was due to linoleic acid, and in other fractions, we found that genipin inhibited ORAI1. Genipin significantly inhibited IORAI1 and interleukin-2 production in CD3/ CD28-stimulated Jurkat T lymphocytes by 35.9% ± 3.02% and 54.7% ± 1.32% at 30 μM, respectively. Furthermore, the same genipin concentration inhibited the proliferation of human primary CD4+ T lymphocytes stimulated with CD3/CD28 antibodies by 54.9% ± 8.22%, as evaluated by carboxyfluorescein succinimidyl ester assay. Our findings suggest that genipin may be one of the active components of GJ responsible for T cell suppression, which is partially mediated by activation of the ORAI1 channel. This study helps us understand the mechanisms of GJ in the treatment of inflammatory diseases.Gardenia jasminoides (GJ) is a widely used herbal medicine with antiinflammatory properties, but its effects on the ORAI1 channel, which is important in generating intracellular calcium signaling for T cell activation, remain unknown. In this study, we investigated whether 70% ethanolic GJ extract (GJEtOH) and its subsequent fractions inhibit ORAI1 and determined which constituents contributed to this effect. Whole-cell patch clamp analysis revealed that GJEtOH (64.7% ± 3.83% inhibition at 0.1 mg/ml) and all its fractions showed inhibitory effects on the ORAI1 channel. Among the GJ fractions, the hexane fraction (GJHEX, 66.8% ± 9.95% at 0.1 mg/ml) had the most potent inhibitory effects in hORAI1-hSTIM1 co-transfected HEK293T cells. Chemical constituent analysis revealed that the strong ORAI1 inhibitory effect of GJHEX was due to linoleic acid, and in other fractions, we found that genipin inhibited ORAI1. Genipin significantly inhibited IORAI1 and interleukin-2 production in CD3/ CD28-stimulated Jurkat T lymphocytes by 35.9% ± 3.02% and 54.7% ± 1.32% at 30 μM, respectively. Furthermore, the same genipin concentration inhibited the proliferation of human primary CD4+ T lymphocytes stimulated with CD3/CD28 antibodies by 54.9% ± 8.22%, as evaluated by carboxyfluorescein succinimidyl ester assay. Our findings suggest that genipin may be one of the active components of GJ responsible for T cell suppression, which is partially mediated by activation of the ORAI1 channel. This study helps us understand the mechanisms of GJ in the treatment of inflammatory diseases.